Analysis of structural behaviour of 3D slender coupled shear wall with opening using ANSYS software - Tan, Hock Hee (2015)
Shear wall is one of the structural system which is used to resist the vertical and the lateral load of the building. Due to the architectural and the ventilation reason, usually there are some opening on shear wall. In most of the apartment building, the size and location of the opening in the shear wall are made without considering the effect on the shear wall and will contribute to the structural failure. The main objectives of this study is to determine the effect of the opening size and its location on shear wall in terms of the crack pattern and drift effect. This study is carried out on 4-storey shear wall building with the help of finite element software, ANSYS 12.0. There are eight model in this analysis which is SW1, SW2, SW3, SW4, SW5, SW6, SW7 and SW8. SW1 are the solid shear wall where the SW2, SW3, SW4, SW5, SW6, SW7 and SW8 was the shear wall with different opening size and location. The model was analyzed by using the lateral uniform distributed load (UDL) at the side of the shear wall. The result shows that the higher the applied load at the shear wall, the higher the deflection. The deflection for SW1, SW2, SW3, SW4, SW5, and SW6 increased by 12.01%, 133.95%, 2.48%, 67.29%, 22.51% and 35.79% respectively when the applied lateral load was increase from 200KPa until 800KPa. While the closer the position of the opening to the applied UDL, the higher the crack pattern of the shear wall. The crack pattern of the shear wall start at the base of the shear wall which was the fixed support, and also the edge of the opening.